STUDI LITERATUR: KESINAMBUNGAN ANTARA IMPLEMENTASI MODEL AISAS DENGAN KODE ETIK ARSITEKTUR INDONESIA - Adrianus Tirta (Business Administration Department - Universitas Katolik Parahyangan, 2022)
Digital business in Indonesia has been growing rapidly over the last few years. Google, Temasek, and Bain & Company forecast that the value of the digital economy in Indonesia will reach USD 146 billion by 2025, making up 40.22% of the total digital economy in Southeast Asia. This digital development occurs in several industries, one of which is the architecture industry. Indonesian architects began to conduct digital activities, especially for communicating with the public. The practice will develop the architectural industry, but there is an indication of problems related to violations of the Architectural Code of Ethics summarized by the Indonesian Architects Association (IAI). Some of the digital practices of Indonesian architects are suspected to have violated several components in the Code of Ethics. This can lead to the revocation of the STRA certification, which will cause problems with the legality of the practice of Indonesian architecture. Using the literature study method, this paper analyzes the components of the Architectural Code of Ethics with the digital practices of Indonesian architects which are summarized using the AISAS Model. The results of the paper show that with certain approaches, digital practices will not violate the Code of Ethics.